Molecular cloning of heat shock protein 10 (Hsp10) and 60 (Hsp60) cDNAs from Galeruca daurica (Coleoptera: Chrysomelidae) and their expression analysis. Issue 4 (30th October 2017) - Tan, Y.; Zhang, Y.; Huo, Z.-J.; Zhou, X.-R.; Pang, B.-P.
Abstract: Galeruca daurica (Joannis) is a new outbreak pest in the Inner Mongolia grasslands in northern China. Heat shock protein 10 and 60 (Hsp10 and Hsp60) genes of G. daurica, designated as GdHsp10 and GdHsp60, were cloned by rapid amplification of cDNA ends techniques. Sequence analysis showed that GdHsp10 and GdHsp60 encoded polypeptides of 104 and 573 amino acids, respectively. Sequence alignment and phylogenetic analysis clearly revealed that the amino acids of GdHsp10 and GdHsp60 had high homology and were clustered with other Hsp10 and Hsp60 genes in insects which are highly relative with G. daurica based on morphologic taxonomy. The mRNA expression analysis by real-time PCR revealed that GdHsp10 and GdHsp60 were expressed at all development stages and in all tissues examined, but expressed highest in eggs and in adults' abdomen; both heat and cold stresses could induce mRNA expression of GdHsp10 and GdHsp60 in the 2nd instar larvae; the two Hsp genes were expressed from high to low with the extension of treatment time in G. daurica eggs exposed to freezing point. Overall, our study provides useful information to understand temperature stress responses of Hsp60 and Hsp10 in G. daurica, and provides a basis to further study functions of Hsp60/Hsp10 relative to thermotolerance and cold hardiness mechanism.